Analysis of sociodemographic and clinical factors associated with Lassa fever disease and mortality in Nigeria - Adebola T. Olayinka; Kelly Elimian; Oladipupo Ipadeola; Chioma Dan-Nwafor; Jack Gibson; Chinwe Ochu; Yuki Furuse; Akanimo Iniobong; Adejoke Akano; Lorna Enenche; Michael Onoja; Chukwuemeka Uzoho; et al. (Public Library of Science (PLoS), 2022)
Over past decades, there has been increasing geographical spread of Lassa fever (LF) cases across Nigeria and other countries in West Africa. This increase has been associated with significant morbidity and mortality despite increasing focus on the disease by both local and international scientists. Many of these studies on LF have been limited to few specialised centres in the country. This study was done to identify sociodemographic and clinical predictors of LF disease and related deaths across Nigeria. We analysed retrospective surveillance data on suspected LF cases collected during January-June 2018 and 2019. Multivariable logistic regression analyses were used to identify the factors independently associated with laboratory-confirmed LF diagnosis, and with LF-related deaths. There were confirmed 815 of 1991 suspected LF cases with complete records during this period. Of these, 724/815 confirmed cases had known clinical outcomes, of whom 100 died. LF confirmation was associated with presentation of gastrointestinal tract (aOR 3.47, 95% CI: 2.79-4.32), ear, nose and throat (aOR 2.73, 95% CI: 1.80-4.15), general systemic (aOR 2.12, 95% CI: 1.65-2.70) and chest/respiratory (aOR 1.71, 95% CI: 1.28-2.29) symptoms. Other factors were being male (aOR 1.32, 95% CI: 1.06-1.63), doing business/trading (aOR 2.16, 95% CI: 1.47-3.16) and farming (aOR 1.73, 95% CI: 1.12-2.68). Factors associated with LF mortality were a one-year increase in age (aOR 1.03, 95% CI: 1.01-1.04), bleeding (aOR 2.07, 95% CI: 1.07-4.00), and central nervous manifestations (aOR 5.02, 95% CI: 3.12-10.16). Diverse factors were associated with both LF disease and related death. A closer look at patterns of clinical variables would be helpful to support early detection and management of cases. The findings would also be useful for planning preparedness and response interventions against LF in the country and region.